Effect of loading 5-phenyl-4H-1, 2, 4-triazole-3-thiol onto polypyrrole chitosan core shell nanoparticles on release rate, antimicrobial, and antitumor activities. (March 2017) - Salahuddin, Nehal; Elbarbary, Ahmed A; Salem, Mohamed L; Elksass, Samar
Polypyrrole chitosan core shell nanoparticles were synthesized by in situ oxidation polymerization of pyrrole using FeCl3 in chitosan aqueous solution. 5-Phenyl-4H-1, 2, 4-triazole-3-thiol (I) was prepared and loaded into polypyrrole chitosan core shell nanoparticles at two different temperatures (25°C and 80°C). These core shell nanoparticle systems are insoluble in acidic medium and have good adsorption capacity. The release of loaded triazole was studied in different pH media (2, 7.4). The mechanism of triazole release was determined by applying zero-order release, first-order release, Higuchi model, Hixson–Crowell, and Korsmeyer–Peppas kinetics equations. The antibacterial activities against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis were evaluated. The potential cytotoxicity against Ehrlich ascites carcinoma cells and liver (HEPG2) cell line in vitro was tested.